2016
DOI: 10.1097/jcn.0000000000000219
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Age Differences Associated With Prehospital Delay in Chinese Patients Presenting With ST-Elevation Myocardial Infarction

Abstract: Male elderly patients (aged ≥65 years) and women (aged ≤64 and ≥75 years) with STEMI were more likely to delay seeking timely medical care. These gender and age differences were explained by different education, stable income, medical insurance, typical chest pain, and cognition toward heart diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 26 publications
5
17
1
3
Order By: Relevance
“…Furthermore, in univariate analysis, the arrival time was prolonged in those with low education; however, in multivariate analysis, education level did not lead to any significant differences in arrival time. Since this finding is inconsistent with those of other previous studies,394041 an analysis of more patients would be required to assess arrival time by education level. Nonetheless, since those with low education made decisions late to seek medical assistance at a hospital, these late decisions would have led to ER arrival delays.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, in univariate analysis, the arrival time was prolonged in those with low education; however, in multivariate analysis, education level did not lead to any significant differences in arrival time. Since this finding is inconsistent with those of other previous studies,394041 an analysis of more patients would be required to assess arrival time by education level. Nonetheless, since those with low education made decisions late to seek medical assistance at a hospital, these late decisions would have led to ER arrival delays.…”
Section: Discussioncontrasting
confidence: 79%
“…Moser, et al17 found no differences by education level. However, some studies394041 that did not assess male and female participants separately reported that education level exerted significant influences on the decision time to seek medical assistance at a hospital, and, as in the present study, the delay in these studies could have been further prolonged in female patients. Late decisions in poorly educated female patients may be due to aging and lack of knowledge of symptoms for AMI.…”
Section: Discussionmentioning
confidence: 42%
“…Истраживања су показала да и поред могућих узрока ових разлика, попут чешћих случајева атипичног испољавања, као и веће учесталости коморбидитета код жена и старијих пацијената, разлика и даље постоји (18). Једно могуће објашњење јесте то да особе женског пола, као и старији пацијенти, чекају дуже време пре него што одлуче да се јаве лекару због бола или нелагоде у грудима (19).…”
Section: Results When We Analyzed 1632 Calls Based Onunclassified
“…Највећа разлика у чекању позива код диспечера пре давања налога екипи на извршење постоји између особа мушког и женског пола и особа мушког пола млађег и старијег животног доба (више од два минута) (табела 2). Још један фактор који би могао да услови овакву неједнакост у приступу јесте чињеница да како жене, тако и старији пацијенти, чекају дуже од тренутка почетка тегоба до момента контактирања здравствених установа (19)(20)(21)(22).У нашем истраживању особе млађе животне доби до 65 година краће чекају од особа старијег животног доба да се позив уручи екипи на извршење. То је показано и у истраживању у Хитној медицинској помоћи из 2012 године (23).…”
Section: слика 1 однос особа мушког и женског пола у истраживаној групиunclassified
“…As previously described,[13] in the first period, STEMI patients who presented at 12 secondary hospitals located in rural areas of China's Liaoning province were consecutively recruited from June 2009 to June 2010. Physicians would complete a purposed-designed questionnaire after written informed consent was obtained from patients or their families.…”
Section: Methodsmentioning
confidence: 99%